(untitled) (Research, Society and Development, 2022)
Introduction: The importance of prescription drugs in dentistry is well established in the literature, although there are few publications regarding pharmacological protocols. The large number of medications offered to the dental surgeon (CD), with their respective indications, dosages, contraindications and adverse effects, add insecurities when choosing the most appropriate medication. Objective: Elaboration of a pharmacotherapeutic protocol, using as a means to obtain this protocol a QR code, accessed through mobile electronic devices. Method: evaluation of the incidence of drug use in the areas of minor oral surgery, endodontics (and endodontic urgencies), periodontics, pediatric dentistry and as antibiotic prophylaxis. Using as inclusion criteria articles, books and bulletins of ANVISA between the years of 2006 to 2016. Results: Elaboration of a medical protocol for adult and child use based on dentistry according to recent literature, using as a means of disclosure and access a code of QR code, accessible through mobile electronic devices. Conclusion: The use of a digital / electronic method, where large numbers of professionals and students of dentistry have access, collaborates for both in decision making at the moment of prescription of a drug, ensuring the knowledge of the most frequent drugs in dentistry.